2006
DOI: 10.1111/j.1574-0862.2006.00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal pest control in greenhouse production of ornamental crops

Abstract: In this study, we develop a conceptual bioeconomic model of floriculture production with aesthetic benefits, wherein optimal decision rules depend on an intertemporal economic objective to maximize profits subject to economic and biological processes. Necessary conditions of the model identify optimal trajectories (e.g., simultaneous, single, or cycling controls) that define decision rules and economic thresholds for profit maximizing growers producing crops with aesthetic attributes. The necessary conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Moffit [17] provides a good overview of break-even pest control (i.e. revenues equal costs implying profit is zero), while Schumacher et al [5] identifies marginal pest thresholds (i.e. intertemporal profit maximization behaviour).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moffit [17] provides a good overview of break-even pest control (i.e. revenues equal costs implying profit is zero), while Schumacher et al [5] identifies marginal pest thresholds (i.e. intertemporal profit maximization behaviour).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, presence of an insect on a plant is often perceived as a signal of lower quality that leads to a lower willingness to pay (WTP) for the product by the consumer. Schumacher et al [5] economically identified aesthetic benefits derived from the visual presence of pests and predators in production of ornamental greenhouse crops. Their analysis suggests that educating consumers about the benefits of predators on ornamental crops (i.e.…”
Section: Consumersmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent work focuses on optimal management of invasive species across time and space (Brown and Zilberman, 2002;Ceddia et al, 2009). Some work has added a predaceous Ecological Economics 107 (2014) [104][105][106][107][108][109][110][111][112][113] insect population, but without considering pesticide toxicity to the predator (Marsh et al, 2000;Schumacher et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In the case study of TSSM control in ivy geranium, Schumacher et al. () pointed out that a grower can reduce the frequency of chemical applications by introducing predators of TSSM. However, their study was done in the context of green house plants and primary–secondary pest problem was not addressed.…”
Section: Introductionmentioning
confidence: 99%